Before the divide : Hindi and Urdu literary culture - Orsini, Francesca (New Delhi : Orient BlackSwan, 2010)
Transcript of papers presented at a workshop chiefly on Hindi and Urdu poetry; covers the period, 9th to 19th century.
Includes bibliographical references (p. [279]-295) and index.
Includes passages in Hindi and Urdu
Keywords: Hindi poetry -- History and criticism -- Congresses; Urdu poetry -- History and criticism -- Congresses; Literature and society -- India -- History -- Congresses; India -- Intellectual life -- Congresses